Cp2ZrMeCl: A reagent for asymmetric methyl addition. - Fletcher, S; Garrec, K (American Chemical Society, 2016)
The use of Cp2ZrMeCl is described as a source of nucleophilic methyl in asymmetric catalysis. This easily prepared reagent is bench stable, weighable in air, and generally useful in highly enantioselective copper-catalyzed addition reactions at room temperature. Methyl is successfully (generally > 90% ee) added in 1,4-additions to cyclic and acyclic α,β-unsaturated ketones, to provide tertiary and quaternary centers. Examples of catalyst controlled diastereoselective 1,6-addition and dynamic kinetic asymmetric allylic alkylation reactions are also reported. The reagent is used in the catalytic asymmetric synthesis of naturally occurring fragrance (R)-(−)-muscone (82% yield, 91% ee).